1993
DOI: 10.1093/carcin/14.12.2501
|View full text |Cite
|
Sign up to set email alerts
|

Reduced autophagic activity in primary rat hepatocellular carcinoma and ascites hepatoma cells

Abstract: Autophagy, measured as the sequestration of an endogenous cytosolic enzyme (LDH), showed a progressive rate reduction during diethylnitrosamine-induced rat liver carcinogenesis. In primary hepatocellular carcinomas the autophagic activity was only one-fourth of that seen in normal hepatocytes. Reduced autophagy was also observed in peritumorous hepatocytes and in cells from preneoplastic liver, and a complete suppression of autophagic protein degradation was seen in normal hepatocytes treated with ascitic flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 0 publications
7
82
0
4
Order By: Relevance
“…Autophagy displays a dual conflicting function in cancer cell biology. We have shown that HCC down-regulates autophagic activity (39,40), and recently, autophagy has been proposed as a tumor suppression mechanism, underlying the possibility that activation of autophagy reverses the neoplastic phenotype (25,41). On the contrary, in the present article, inhibition of autophagy enhanced apoptosis, indicating that autophagy contributes to tumor progression as a protective mechanism against stressful conditions (25,42,43).…”
Section: Discussionmentioning
confidence: 98%
“…Autophagy displays a dual conflicting function in cancer cell biology. We have shown that HCC down-regulates autophagic activity (39,40), and recently, autophagy has been proposed as a tumor suppression mechanism, underlying the possibility that activation of autophagy reverses the neoplastic phenotype (25,41). On the contrary, in the present article, inhibition of autophagy enhanced apoptosis, indicating that autophagy contributes to tumor progression as a protective mechanism against stressful conditions (25,42,43).…”
Section: Discussionmentioning
confidence: 98%
“…A striking example of how reduced autophagic proteolysis can contribute to cell growth can be found in the development of liver carcinogenesis. This decrease in autophagic flux results from a decrease in the rate of autophagic sequestration and is already detectable in the early preneoplastic stage (Schwarze & Seglen, 1985;Yucel et al, 1989;Kisen et al, 1993). Autophagic flux is then hardly inhibitable by amino acids nor is it inducible by catabolic stimuli (Schwarze & Seglen, 1985;Tessitore et al, 1988;Kisen et al, 1993) and declines in the more advanced stage of cancer development to a rate of less than 20% of that seen in normal hepatocytes (Kisen et al, 1993).…”
Section: Autophagy and Carcinogenesismentioning
confidence: 99%
“…This decrease in autophagic flux results from a decrease in the rate of autophagic sequestration and is already detectable in the early preneoplastic stage (Schwarze & Seglen, 1985;Yucel et al, 1989;Kisen et al, 1993). Autophagic flux is then hardly inhibitable by amino acids nor is it inducible by catabolic stimuli (Schwarze & Seglen, 1985;Tessitore et al, 1988;Kisen et al, 1993) and declines in the more advanced stage of cancer development to a rate of less than 20% of that seen in normal hepatocytes (Kisen et al, 1993). The fact that the addition of 3-methyladenine to hepatocytes from normal rats increased hepatocyte viability to the same level as observed for the tumour cells (Schwarze & Seglen, 1985) strongly suggests that the fall in autophagic proteolysis contributes to the rapid growth rate of these cells and gives them a selective advantage over the normal hepatocytes.…”
Section: Autophagy and Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…As controversial as it sounds, there is evidence that autophagy might have roles in both tumor suppression and tumor progression as extensively reviewed in other papers [3,[53][54][55]. Some studies have shown that the activity of the autophagic pathway decreases in most cancerous cells [56,57], suggesting that autophagy might be a suppressive mechanism for cancer progression. The tumor-suppressive effect of autophagy might be conferred by increased protein degradation and/or by the clearance of damaged organelles from the cytosol.…”
Section: Autophagy and Cancermentioning
confidence: 99%